Efektifitas Pelayanan Pembayaran Pajak Kendaraan Bermotor (PKB) Drive Thru di Kota Makassar - SAKIR, AHMAD ROSANDI (Universitas Kapuas Sintang, 2024)
This study aims to analyze and describe the implementation of public services for Motor Vehicle Tax (PKB) payments and to identify the supporting and inhibiting factors of the PKB Drive Thru service implementation in Makassar City. The method used is qualitative with a descriptive research type. Data collection was carried out through observation, interviews, and documentation related to the implementation of the PKB Drive Thru Public Service in Makassar City. The study participants totaled nine people. The results of the study show that the aspects of Communication, Resources, Disposition, and Bureaucratic Structure at SAMSAT in Makassar City can be considered good. The communication conducted by SAMSAT in conveying information regarding the validation of vehicle registration certificates (STNK), PKB payments, and mandatory insurance contributions (SWDKLLJ) through the PKB Drive Thru service is deemed effective, with the clarity of information being accountable through various media such as the agency's website, newspapers, radio, and social media.